Investments in ICT-capital and economic performance of small and medium scale enterprises in East Africa - Chowdhury, Shyamal K. (Wiley, 2006)
In this paper, we focused on whether investments in ICTs could cause any increases in a firm's performance. We constructed a data set for two East African countries—Kenya and Tanzania for small and medium scale enterprises and focused on three performance indicators—internal rate of return, labour productivity and domestic and export market expansion. Findings of this paper suggested that investments in ICT have a positive impact on general market expansion. However, it has a negative impact on labour productivity, and such investment does not have any significant impact on the firm's return nor does it determine the firm's exporter (non‐exporter) status. Copyright © 2006 John Wiley & Sons, Ltd.